2024
DOI: 10.1177/20543581241235526
|View full text |Cite
|
Sign up to set email alerts
|

Royal Jelly, A Super Food, Protects Against Celecoxib-Induced Renal Toxicity in Adult Male Albino Rats

Hesham A. M. I. Khalifa,
Naglaa Z. H. Eleiwa,
Heba A. Nazim

Abstract: Background: Celecoxib is a COX-2 nonsteroidal anti-inflammatory drug (NSAID). It is widely used for the treatment of osteoarthritis, rheumatoid arthritis, and ankylosing spondylitis. Objective: This study aimed to explore the effect of long-term administration of celecoxib on kidney of male albino rats, and to study the potential effect of treatment discontinuation on such tissues. The study also examined the alleged ameliorative effect of royal jelly (RJ). Methods: Fifty, male albino rats were divided into 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Apart from chemotherapy and radiation, previous studies reported the in vivo protective and antioxidative roles of RJ against CCl4, oxymetholone, paracetamol, celecoxib, and fumonisin-induced liver and kidney injury, without identifying the responsible components [ 270 , 285 , 286 , 287 , 288 , 289 , 290 , 291 ].…”
Section: Biological Function Of Royal Jellymentioning
confidence: 99%
“…Apart from chemotherapy and radiation, previous studies reported the in vivo protective and antioxidative roles of RJ against CCl4, oxymetholone, paracetamol, celecoxib, and fumonisin-induced liver and kidney injury, without identifying the responsible components [ 270 , 285 , 286 , 287 , 288 , 289 , 290 , 291 ].…”
Section: Biological Function Of Royal Jellymentioning
confidence: 99%